Los efectos macroeconómicos de la privatización: un modelo - Alarcón Espinoza, Giovann (2001)
During the last decade of the Twentieth century Peru has undertaken a public firms' privatization process involving the transfer of ownership at firms producing intermediate goods to foreign investors. This essay proposes a model for assesing the macroeconomic effects produced by the privatization of this kind of companies on the telecommunication industry. By using National income as a reference unit for measuring impacts, the model captures analytically, as short-term effects the rise in the relative prices of telephone services along with the transfer of poverty and the filling of the market gap led by the raise in service coverage. Furthermore, the model finds in the long-term a positive effect from the consequences of technological innovation at the sector, in the end a source of endogenous growth. Synthesizing, the essay concludes that a priori it is impossible to determine the nature of the overall effect from the sector's privatization, for it will depend on the prevalence of certain economic conditions identified on the model.